Optimal Treatment Timing in Orthodontics: A Scoping Review - Hamidaddin, Mohammad A. (European Journal of Dentistry, 2023)
The appropriate timing for orthodontic intervention has been a subject of debate for a long time, concerning not only the immediate effects but also the long-term benefits of such treatment. This review aimed to find the appropriate treatment timing for the intervention of various orthodontic problems. A literature search was performed in all major databases, including PubMed and Cochrane Library, until February 20, 2023. All observational and experimental studies published in English that compared early versus late orthodontic treatment in different types of orthodontic problems were included. Data selection and charting were undertaken by a single investigator. A total of 32 studies were identified that discussed various aspects of interventions, including Class II and Class III malocclusion, pseudo-Class III malocclusion, anterior and posterior crossbite, extractions, and long-term benefits. Overall, early intervention was not found to be superior in terms of effectiveness, overall duration of appliances, and cost–benefit ratio. Early intervention should be reserved for specific conditions or localized malocclusions that have psycho-social benefits, or to significantly reduce the severity of problems to be dealt with in comprehensive treatment in the permanent dentition.
Keywords: early orthodontic treatment; Early intervention; late treatment